Comparative Study of SiO2, Al2O3, and BeO Ultrathin Interfacial Barrier Layers in Si Metal-Oxide-Semiconductor Devices - J. H. Yum; J. Oh; Todd. W. Hudnall; C. W. Bielawski; G. Bersuker; S. K. Banerjee (Active and Passive Electronic Components)
In a previous study, we have demonstrated that beryllium oxide (BeO) film grown by atomic layer deposition (ALD) on Si and III-V MOS devices has excellent electrical and physical characteristics. In this paper, we compare the electrical characteristics of inserting an ultrathin interfacial barrier layer such as SiO2, Al2O3, or BeO between the HfO2 gate dielectric and Si substrate in metal oxide semiconductor capacitors (MOSCAPs) and n-channel inversion type metal oxide semiconductor field effect transistors (MOSFETs). Si MOSCAPs and MOSFETs with a BeO/HfO2 gate stack exhibited high performance and reliability characteristics, including a 34% improvement in drive current, slightly better reduction in subthreshold swing, 42% increase in effective electron mobility at an electric field of 1 MV/cm, slightly low equivalent oxide thickness, less stress-induced flat-band voltage shift, less stress induced leakage current, and less interface charge.